Polyphenic trait promotes liver cancer in a model of epigenetic instability in mice. Issue 1 (18th May 2017) - Cassano, Marco; Offner, Sandra; Planet, Evarist; Piersigilli, Alessandra; Jang, Suk Min; Henry, Hugues; Geuking, Markus B.; Mooser, Catherine; McCoy, Kathy D.; Macpherson, Andrew J.; Trono, Didier
Abstract : Hepatocellular carcinoma (HCC) represents the fifth‐most common form of cancer worldwide and carries a high mortality rate attributed to lack of effective treatment. Males are 8 times more likely to develop HCC than females, an effect largely driven by sex hormones, albeit through still poorly understood mechanisms. We previously identified TRIM28 (tripartite protein 28), a scaffold protein capable of recruiting a number of chromatin modifiers, as a crucial mediator of sexual dimorphism in the liver. Trim28 hep–/– mice display sex‐specific transcriptional deregulation of a wide range of bile and steroid metabolism genes and development of liver adenomas in males. We now demonstrate that obesity and aging precipitate alterations of TRIM28‐dependent transcriptional dynamics, leading to a metabolic infection state responsible for highly penetrant male‐restricted hepatic carcinogenesis. Molecular analyses implicate aberrant androgen receptor stimulation, biliary acid disturbances, and altered responses to gut microbiota in the pathogenesis of Trim28 hep–/– ‐associated HCC. Correspondingly, androgen deprivation markedly attenuates the frequency and severity of tumors, and raising animals under axenic conditions completely abrogates their abnormal phenotype, even upon high‐fat diet challenge. Conclusion : This work underpins how discrete polyphenic traits in epigenetically metastable conditions can contribute to a cancer‐prone state and more broadly provides new evidence linking hormonal imbalances, metabolic disturbances, gut microbiota, and cancer. (Hepatology 2017;66:235–251).